A Rare Case of Pulmonary Restrictive Syndrome after Liquid Silicone Injection: The Role of the Plastic Surgeon - Bonfirraro, Pier Paolo; Sallam, Davide; Verga, Maurizio; Righi, Bernardo; Mevio, Gabriele; Codazzi, Denis; Leone, Francesco; Carminati, Marcello (Indian Journal of Plastic Surgery, 2021)
Despite being especially used in its solid form, silicone is still injected as a liquid filler for breast contouring in many countries. Here, we present a rare case of a woman with silicone pneumonitis and extended breast scarring after breast silicone injection. Because of evidence of a restrictive syndrome due to the thoracic extensive scarring tissue and the high demand of oxygen therapy, as jointly agreed with the pulmonologists, we decided to perform a surgical asportation of the scarring tissue and covering with microsurgical flap. We chose the deep inferior epigastric perforator flap mainly because of the large amount of skin that is possible to use, the good skin texture matching, and the possibility of double team working without changing patient’s position.
Keywords: silicone breast injection; silicone pneumonitis; deep inferior epigastric perforator flap